The Influence of Population, Open Unemployment Rate and Human Development Index on Poverty Levels in West Kalimantan Province - Firmansyah, Riki Zogik; Huda, Syamsul (Indonesian Journal of Advanced Research, 2025)
This study analyzes the effect of population, open unemployment rate (TPT), and human development index (HDI) on the poverty rate in West Kalimantan Province. Using a quantitative approach with secondary data from BPS for the period 2009-2023, the method used is multiple linear regression. The results show that population and HDI have a negative significant effect on poverty, while TPT has no significant effect. This finding confirms the importance of improving the quality of human resources and population management in reducing poverty.